2014
DOI: 10.5653/cerm.2014.41.2.86
|View full text |Cite
|
Sign up to set email alerts
|

Serum luteinizing hormone level and luteinizing hormone/follicle-stimulating hormone ratio but not serum anti-Müllerian hormone level is related to ovarian volume in Korean women with polycystic ovary syndrome

Abstract: ObjectiveThe aim of the present study was to investigate the relationship between ovarian follicle count and volume on ultrasonography and serum hormone levels including the levels of the anti-Müllerian hormone (AMH) and gonadotropin in women with the polycystic ovary syndrome (PCOS).MethodsA total of 118 Korean women aged 18-35 years who were newly diagnosed with PCOS at a university hospital were included in this study. Serum LH, FSH, and AMH levels were measured in the early follicular phase, and the total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 28 publications
4
18
0
Order By: Relevance
“…In the current study, we categorized all participants into three groups according to the LH/FSH ratio: group 1 (LH/FSH ratio <1.0), group 2 (1.0≤ LH/FSH ratio <2.0), and group 3 (LH/FSH ratio ≥2.0). In this study, participants with higher LH/FSH ratios showed higher total antral follicle counts and larger total ovarian volume, and these findings are in agreement with those of previous studies [1516222324]. …”
Section: Discussionsupporting
confidence: 93%
“…In the current study, we categorized all participants into three groups according to the LH/FSH ratio: group 1 (LH/FSH ratio <1.0), group 2 (1.0≤ LH/FSH ratio <2.0), and group 3 (LH/FSH ratio ≥2.0). In this study, participants with higher LH/FSH ratios showed higher total antral follicle counts and larger total ovarian volume, and these findings are in agreement with those of previous studies [1516222324]. …”
Section: Discussionsupporting
confidence: 93%
“…Accordingly, several threshold AMH values for PCOS (based on measurements among varied age and ethnic groups) have been proposed. Of note, serum AMH has been considered as a substitute for antral follicle count as articulated by the Rotterdam diagnostic criteria for PCOS (4)(5)(6)(7)(8)(9)(10)(11)(12) although this has not been widely used perhaps due to the lack of a universally standardized AMH serum assay (13).…”
mentioning
confidence: 99%
“…Both the AMH concentration and the LH/ FSH ratio are significantly correlated with the AFC in patients with PCOS. 10 Women with PCOS have high AMH concentrations, whereas those with DOR have low AMH concentrations. Because of the varying sensitivity and specificity, the AMH has yet to be adopted as part of the diagnostic criteria for PCOS.…”
Section: Discussionmentioning
confidence: 99%